LESSONS FROM CISCO’S ACQUISITION INTEGRATION (Word Count: 5287 words) - Sridhar, Geetha (2012)
Mergers and acquisitions (M & A) are the buzz words for corporates worldwide. The object of mergers and acquisition is to increase the value of the company as it takes long time to create value through organic growth. The purpose of merger/acquisition could be for expanding the company’s operations to new markets, economies of scale or scope, acquire new products or capabilities. Investopedia defines ‘Merger’ as the combining of two or more companies, generally by offering the stockholders of one company securities in the acquiring company in exchange for the surrender of their stock. Acquisition is defined by Investopedia as ‘A corporate action in which a company buys most, if not all, of the target company's ownership stakes in order to assume control of the target firm. Mergers and acquisitions are used synonymously though there is a line of difference between the two, where acquisition is takeover of one company by another and clearly establishes itself as the new owner.